Publications Received (Academy of Management Review, 1989)
The article presents a list of business publications received by the journal. They include “An Audit of the Case Study Method,” by Michael Masoner, “Business Forecasting Methods,” by Jeffrey Jarrett, and “Decisions and Organizations,” by James G. March.